CHALLENGES IN IMPLEMENTING EDUCATION POLICY: TEACHER READINESS, SCHOOL INFRASTRUCTURE, AND INTER-INSTITUTIONAL COORDINATION AS MAJOR OBSTACLES IN IMPLEMENTING NEW POLICIES: A LITERATURE REVIEW METHOD - Ana Theriana; Al-Amin (International Journal of Teaching and Learning, 2025)
This study aims to analyse the main challenges in implementing new education policies in Indonesia, focusing on teacher readiness, limited school infrastructure, and inter-institutional coordination as the main obstacles. The method used is a systematic literature review of various journal articles, policy reports, and empirical studies published between 2015 and 2025. The results of the analysis show that teacher readiness, which includes pedagogical competence and mental preparedness, is crucial to the effectiveness of policy implementation. In addition, disparities in educational infrastructure between urban and remote areas also hinder the equitable implementation of policies. Another crucial obstacle is the weak coordination between institutions, which hinders programme synchronisation and communication, thereby affecting the smooth implementation of policies. This study concludes that education reform efforts must prioritise strengthening teacher capacity, improving the quality and equity of infrastructure, and managing cross-institutional coordination. A holistic and collaborative approach is key to the successful implementation of new education policies in Indonesia.